Densa Ann Shaj - Synthesis of affordable activated carbons from almond shell and almond tree pruning waste for aqueous zinc hybrid supercapacitors. (Jornada de Jóvenes Investigadores del I3A, 2025)
Synthesis of affordable activated carbons from almond shell and almond tree pruning waste for aqueous zinc hybrid supercapacitors.